2024
DOI: 10.3389/fncel.2023.1332179
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 (IGF-2) rescues social deficits in NLG3–/y mouse model of ASDs

Rocco Pizzarelli,
Domenico Pimpinella,
Christian Jacobs
et al.

Abstract: Autism spectrum disorders (ASDs) comprise developmental disabilities characterized by impairments of social interaction and repetitive behavior, often associated with cognitive deficits. There is no current treatment that can ameliorate most of the ASDs symptomatology; thus, identifying novel therapies is urgently needed. Here, we used the Neuroligin 3 knockout mouse (NLG3–/y), a model that recapitulates the social deficits reported in ASDs patients, to test the effects of systemic administration of IGF-2, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous data revealed that Nlgn3 KO mice treated with IGF-2 fully recovered the social novelty discrimination. This effect was not accompanied by any alteration in spontaneous glutamatergic synaptic transmission within the CA2 region, but rather by enhanced CA2 neuronal excitability ( 283 ). Similarly, the administration of IGF-2 ameliorated social interaction deficits in BTBR mice and enhanced their social novelty memory via hippocampal IGF-2 receptor ( 261 ).…”
Section: Therapies That Positively Influence the Structure And Functi...mentioning
confidence: 99%
“…Previous data revealed that Nlgn3 KO mice treated with IGF-2 fully recovered the social novelty discrimination. This effect was not accompanied by any alteration in spontaneous glutamatergic synaptic transmission within the CA2 region, but rather by enhanced CA2 neuronal excitability ( 283 ). Similarly, the administration of IGF-2 ameliorated social interaction deficits in BTBR mice and enhanced their social novelty memory via hippocampal IGF-2 receptor ( 261 ).…”
Section: Therapies That Positively Influence the Structure And Functi...mentioning
confidence: 99%